2023
DOI: 10.1002/ejhf.3018
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and metabolic phenotyping of patients with aortic stenosis and preserved ejection fraction: A specific phenotype of heart failure with preserved ejection fraction?

Nicolò De Biase,
Matteo Mazzola,
Lavinia Del Punta
et al.

Abstract: BackgroundDegenerative aortic valve stenosis with preserved left ventricular ejection fraction (ASpEF) and heart failure with preserved left ventricular ejection fraction (HFpEF) display intriguing similarities. We designed this study to provide a non‐invasive, comparative analysis of ASpEF versus HFpEF at rest and during exercise.Methods and resultsWe prospectively enrolled 148 patients with HFpEF and 150 patients with degenerative moderate‐to‐severe ASpEF, together with 66 age‐ and sex‐matched healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…7,8 The role of EAT appears to be related to inflammation, mechanical effects, and its proximity to the heart and major blood vessels. In the study of De Biase et al, 1 greater EAT thickness showed an inverse correlation with peak VO 2 at cardiopulmonary exercise testing in both HFpEF and AS. When analysing the AS cohort, EAT thickness was directly related to indices of valve disease severity, including peak transvalvular velocity, mean transvalvular pressure gradient (at rest and peak exercise), and aortic valve calcium score and volume.…”
Section: As and Hfpefmentioning
confidence: 85%
See 1 more Smart Citation
“…7,8 The role of EAT appears to be related to inflammation, mechanical effects, and its proximity to the heart and major blood vessels. In the study of De Biase et al, 1 greater EAT thickness showed an inverse correlation with peak VO 2 at cardiopulmonary exercise testing in both HFpEF and AS. When analysing the AS cohort, EAT thickness was directly related to indices of valve disease severity, including peak transvalvular velocity, mean transvalvular pressure gradient (at rest and peak exercise), and aortic valve calcium score and volume.…”
Section: As and Hfpefmentioning
confidence: 85%
“…In this issue of the Journal, De Biase et al 1 compare the haemodynamic and metabolic characteristics of patients with degenerative severe AS versus patients with HFpEF. Patients with AS (n = 150) were characterized by isolated aortic valve disease with high transvalvular gradients and preserved left ventricular (LV) ejection fraction, thereby excluding those with low-flow low-gradient AS with reduced LV function, or concomitant mitral valve disease.…”
mentioning
confidence: 99%
“…In addition, CPETecho can reveal noncardiac symptoms and limitations. 34 For instance, a low peak Vo 2 in the absence of ex-PHT could be caused by a diminished breathing reserve or a submaximal test, indicated by a low respiratory exchange ratio. 14,35 Patients with AS denying symptoms in daily life could be considered truly asymptomatic, particularly when they have a normal peak Vo 2 or low mPAP/CO slope.…”
Section: Discussionmentioning
confidence: 99%
“…Functional capacity was similarly impaired in AVS and HFpEF patients due to both peripheral and central components. Epicardial adipose tissue thickness was inversely correlated with peak oxygen consumption in all subjects, was greater and directly related to echocardiography‐derived disease severity and computed tomography‐derived aortic valve calcium burden in patients with AVS and preserved EF 15 …”
Section: Pathophysiologymentioning
confidence: 91%